Meanwhile, to South of the Loire: Sou- thern French chivalrous ideal and the formation of courtesy - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2020)
It is dedicated to the reconstruction of the process of the courteous tradition’s emergence, which had been embodied in the lyrical poetry of troubadours. The aristocratic courtyards of Southern France are analyzed, in the context of the development of which a courteous culture had took shape. The focus is on the analysis of sociocultural factors. determining its formation. The influence of the phenomenon of the medieval city (in particular, the urban mentality) on the development of the courteous tradition is considered. The process of aristocratization of chivalry as laying the foundation for the courteous culture is analyzed. The social status of troubadour in the system of medieval culture is considered.
Keywords: Southern French chivalry; aristocratic courts; courtesy; troubadours; knight and aristocrat; aristocratization of chivalry; ideology of the aristocracy; love lyrics